PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DALAM PROSES PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DENGAN PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBASIS PENDEKATAN TPACK DI KELAS VII C SMP NEGERI 12 KOTA MADIUN TAHUN AJARAN 2024/2025 - Salma, Salsabila Nur; Nuswantari, Nusi; Wismarini, Siti Nursabatun (Universitas Negeri Surabaya (Unesa), 2024)
This research aims to improve students critical thinking skills through the TPACK (Technological, Pedagogical, and Content Knowledge) learning approach in First High Schools (SMP) in the Pancasila and Civic Education subject by applying the problem-based learning (PBL) model. The method used in this research is Classroom Action Research. This classroom action research was carried out through 2 (two) cycles. The subjects of this research were students in class VII-C, totaling 38 students. Data collection through test and observation techniques. Quantitative data analysis is used to analyze the increase in students' critical thinking skills in Pancasila an Civic Education subjects. Based on the research results, it can be concluded that the application of the Problem-Based Learning (PBL) model with the TPACK learning approach can improve the critical thinking abilities of class VII-C students at SMPN 12 Madiun city in the 2024/2025 academic year. Keywords: Critical thinking, Problem Base Learning (PBL), and Technological Pedagogical Content Knowledge (TPACK)